Generalized hysteretic constitutive model of marine structural steel with pitting corrosion. (15th December 2020) - Yang, Yang; Ji, Fei; He, Zheng; Ma, Houbiao; Jia, Ziyue
Abstract: To describe the effect of the coupled damage caused by corrosion and low-fatigue hysteresis on the mechanical performance of marine steel, a generalized hysteretic constitutive model is developed based on the results of a reversed cyclic test that was conducted previously on the commonly used D36 steel considering different corrosion scenarios and loading schemes. Three typical hardening models, namely the NLISO isotropic model, Chaboche kinematic model, and combined hardening model in ABAQUS® are first studied using the parameters calibrated with the test data. The combined model is found to be capable of performing desirable simulations for all pitting corrosion cases. However, it is difficult to explicitly clarify the relation between its parameters and the volume loss ratio (VLR), which is not applicable for general purposes. The developed hysteretic model consists of a cyclic hardening skeleton segment, an unloading segment, and a reloading segment. A direct link is established between its parameters and VLR via regressive analysis. This generalized model can comprehensively account for, with desirable prediction accuracy, the influence of pitting-induced volume loss, stress concentration, and eccentricity on the hysteretic behaviour of marine steel. It can be applied to engineering practice with rational conservation. Highlights: Strain reversals can cause cyclic hardening effect but at the expense of reduced yielding plateau. The parametric determination of the combined model cannot be explicitly clarified. The link between the proposed hysteretic model and volume loss ratio is explicitly established. The proposed model can well address the coupled corrosion-hysteresis damage of marine steel.